2011
DOI: 10.1002/cne.22559
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of the structural basis of the ascending arousal system

Abstract: The “ascending reticular activating system” theory proposed that neurons in the upper brainstem reticular formation projected to forebrain targets that promoted wakefulness. More recent formulations have emphasized that most neurons at the pontomesencepahlic junction that participate in these pathways are actually in monoaminergic and cholinergic cell groups. However, cell-specific lesions of these cell groups have never been able to reproduce the deep coma seen after acute paramedian midbrain lesions that tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
363
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 458 publications
(387 citation statements)
references
References 69 publications
(138 reference statements)
20
363
3
1
Order By: Relevance
“…not significant population activity that may be the reason for the reduced amplitude of the low-frequency-evoked LFP responses in this condition. LFP power modulations have been previously linked to cortical state, such that the desynchronized state is associated with a reduction in low-frequency power in LFP and EEG signals (Bhattacharyya et al 2013;Buzsaki et al 1988;Chen et al 2015;Fuller et al 2011;McLin et al 2002;Metherate et al 1992;Pinto et al 2013). Low-frequency LFP power reduction has been linked to a general suppression in depth-negative waves, which are large-amplitude low-frequency LFP events that occur spontaneously during anesthesia or quiet wakefulness (Harris and Thiele 2011) in the synchronized state.…”
Section: Discussionmentioning
confidence: 99%
“…not significant population activity that may be the reason for the reduced amplitude of the low-frequency-evoked LFP responses in this condition. LFP power modulations have been previously linked to cortical state, such that the desynchronized state is associated with a reduction in low-frequency power in LFP and EEG signals (Bhattacharyya et al 2013;Buzsaki et al 1988;Chen et al 2015;Fuller et al 2011;McLin et al 2002;Metherate et al 1992;Pinto et al 2013). Low-frequency LFP power reduction has been linked to a general suppression in depth-negative waves, which are large-amplitude low-frequency LFP events that occur spontaneously during anesthesia or quiet wakefulness (Harris and Thiele 2011) in the synchronized state.…”
Section: Discussionmentioning
confidence: 99%
“…These areas a) have widespread forebrain projections with axons traversing the lesion and stimulation region and b) promote waking or wake-associated phenomena [17]. However systematic studies placing lesions in these cell groups have identified only two subcortical regions that are critically required for maintaining a behaviorally responsive state: the basal forebrain and the parabrachial/precoeruleus region [18]. It is likely that one or more of the structures in the arousal network mediates OSA arousal.…”
Section: Arousal Systemmentioning
confidence: 99%
“…This model has directed and shaped research on cortical function and sleep-wake regulation, as well as clinical evaluation of patients with loss of consciousness [40]. The projections from the reticular formation to the central thalamus to the cerebral cortex may constitute a critical pathway for maintaining a waking cortical state [41].…”
Section: Discussionmentioning
confidence: 99%